Protective effect of indoleamines on in vitro ascorbate-Fe2+ dependent lipid peroxidation of rod outer segment membranes of bovine retina - Guajardo, Margarita Haydeé (2003)
Rod outer segment membranes (ROS) are highly vulnerable to autooxidation because of their high content of long chain polyunsaturated fatty acids (PUFAs). Melatonin and N-acetylserotonin are indoleamines synthesized in the pineal gland, retina and other tissues. These compounds are free radical scavengers and indirect antioxidants because of their stimulatory effect on antioxidative enzymes. We compared the in vitro protective effect of melatonin and N-acetylserotonin on the ascorbate-Fe2+ induced lipid peroxidation of PUFAs located in ROS membranes. This process was measured by chemiluminescence and fatty acid composition of total lipids of ROS. We assayed increasing concentrations of melatonin (0-10 mM) and N-acetylserotonin (0-2 mM). In both cases the total cpm originated from light emission (chemiluminescence) was found to be lower in those membranes incubated in the presence of either melatonin or N-acetylserotonin; this decreased proportional to the concentration of the indole. Thus, 10 mM melatonin and 2 mM N-acetylserotonin produced a reduction of 51 ± 6 and 100% in the total chemiluminescene (lipid peroxidation), respectively. We also noticed a PUFAs protection: the docosahexaenoic acid content decreased considerably when the membranes were submitted to oxidative damage. This reduction was from 37.6 ± 2.1% in the native membranes to 6.2 ± 0.8% in those which were peroxidized. These changes were less pronounced in treated ROS membranes; as an example in the presence of 10 mM melatonin or 2 mM N-acetylserotonin we observed a content preservation of 22:6 n-3 (23.6 ± 1.2 and 39.1 ± 1.2% respectively). The concentration of each compound required to inhibit 50% of the lipid peroxidation (IC50) was 9.82 mM for melatonin and 0.43 mM for N-acetylserotonin, respectively. N-acetylserotonin shows a protective effect about 20 times higher than that of melatonin.